Vesicovaginal fistula: an uncommon complication of a perineal burn in a 12-year-old girl - Cheikhrouhou, Taycir; Dhaou, Mahdi Ben; Hbaieb, Manar; Zitouni, Hayet; Mhiri, Riadh (Archives of Case Reports, 2023)
Perineal burns are a rare finding in children that may cause severe complications. Vesicovaginal fistulas are an uncommon complication of a perineal burn that can be a tragedy for girls suffering from them. Fistula and/or its treatment are a socially debilitating problem with significant medicolegal implications. We present a rare case of a girl with a history of traumatic perineal burns who was diagnosed with a vesicovaginal fistula and repaired through a transvaginal approach.